2017
DOI: 10.1186/s12879-017-2494-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of patient screening and isolation on curtailing Clostridium difficile infection in hospital settings

Abstract: BackgroundPatient screening at the time of hospital admission is not recommended as a routine practice, but may be an important strategy for containment of Clostridium difficile infection (CDI) in hospital settings. We sought to investigate the effect of patient screening in the presence of asymptomatic carriers and in the context of imperfect patient isolation.MethodsWe developed and parameterized a stochastic simulation model for the transmission dynamics of CDI in a hospital ward.ResultsWe found that the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…The prevalence of CDI has increased globally due to inappropriate use of antibiotics. Many articles have reported the molecular epidemiology of C. difficile isolated from patients in hospitals, which has been studied extensively as an external source of CDI [6]. Additionally, some human pathogenic PCR ribotypes are found in other mammals, such as pigs, horses, and cattle.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of CDI has increased globally due to inappropriate use of antibiotics. Many articles have reported the molecular epidemiology of C. difficile isolated from patients in hospitals, which has been studied extensively as an external source of CDI [6]. Additionally, some human pathogenic PCR ribotypes are found in other mammals, such as pigs, horses, and cattle.…”
Section: Introductionmentioning
confidence: 99%
“…However, current guidelines do not recommend active surveillance or the isolation of asymptomatic C. di cile carriers as measures to prevent C. di cile transmission. However, several studies have shown that active screening for C. di cile colonization using PCR assays is effective for infection control and prevention of C. di cile infection [10][11][12]. Ongoing research on new strategies, such as screening for asymptomatic C. di cile infections, is needed to optimize the containment of these infections.…”
Section: Discussionmentioning
confidence: 99%
“…Early recognition of toxigenic C. di cile infection on hospital admission is essential for timely infection control measures to contain the transmission of nosocomial CDI [10][11][12]. Asymptomatic toxigenic C. di cile carriers are also a high-risk group for progression to symptomatic CDI, for which antimicrobial stewardship measures should be instituted.…”
Section: Introductionmentioning
confidence: 99%
“…However, data on the prevalence and risk factors for toxigenic C. di cile carriage on hospital admission in older populations are limited.Nucleic acid ampli cation testing (NAAT) is the only diagnostic test for the detection of toxigenic C. di cile used in many studies and may result in CDI overdiagnosis [8]. NAAT screening tools for CDI are, however, widely implemented because asymptomatic toxigenic C. di cile carriage is a major risk factor for CDI [9].Early recognition of toxigenic C. di cile infection on hospital admission is essential for timely infection control measures to contain the transmission of nosocomial CDI [10][11][12]. Asymptomatic toxigenic C. di cile carriers are also at high risk for progression to symptomatic CDI, for which antimicrobial stewardship measures should be implemented.…”
mentioning
confidence: 99%
“…Early recognition of toxigenic C. di cile infection on hospital admission is essential for timely infection control measures to contain the transmission of nosocomial CDI [10][11][12]. Asymptomatic toxigenic C. di cile carriers are also at high risk for progression to symptomatic CDI, for which antimicrobial stewardship measures should be implemented.…”
mentioning
confidence: 99%